2019
DOI: 10.1039/c9na00023b
|View full text |Cite
|
Sign up to set email alerts
|

Truncated octahedral bipyramidal TiO2/MXene Ti3C2 hybrids with enhanced photocatalytic H2 production activity

Abstract: MXene Ti3C2/TiO2 hybrids with a 2D multilayer structure, prepared by calcination of F-terminated Ti3C2, exhibited an enhanced photocatalytic H2-production activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…41,43 MXene surface oxidation is most commonly employed in Ti-based MXenes to form TiO2 photocatalysts, 55 although oxidation can be also applied to V, Nb, and Mo-based MXenes to form their respective oxides. 58,62,82 In-situ oxidation is achieved through flash oxidation (1150 °C, 30 s), 55 prolonged oxidation from calcination (350-650 °C), [85][86][87] hydro/solvothermal processes (120-220 °C), 47,78,[88][89][90][91] or CO2 oxidation (500-900 °C). 62,83 Control over the MXenes' surface Tx groups prior to oxidation is crucial, since different surface terminations have resulted in morphological differences in the oxides formed.…”
Section: Design Strategies For Mxene Hybrids and Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…41,43 MXene surface oxidation is most commonly employed in Ti-based MXenes to form TiO2 photocatalysts, 55 although oxidation can be also applied to V, Nb, and Mo-based MXenes to form their respective oxides. 58,62,82 In-situ oxidation is achieved through flash oxidation (1150 °C, 30 s), 55 prolonged oxidation from calcination (350-650 °C), [85][86][87] hydro/solvothermal processes (120-220 °C), 47,78,[88][89][90][91] or CO2 oxidation (500-900 °C). 62,83 Control over the MXenes' surface Tx groups prior to oxidation is crucial, since different surface terminations have resulted in morphological differences in the oxides formed.…”
Section: Design Strategies For Mxene Hybrids and Compositesmentioning
confidence: 99%
“…Li et al reported that calcining untreated Ti3C2Tx with -O, -F, and -OH terminations resulted in larger anatase TiO2 nanoparticles (NPs) with exposed (001) planes, compared to the smaller and more spherical anatase TiO2 NPs formed by calcining Ti3C2Tx with primarily -OH terminations. 87 With precise control and optimization over the heat treatment conditions, a variety of functional TiO2/MXene hybrids can be formed with high PC activity toward water splitting, CO2RR, and N2RR. 87,89 For example, Ti3C2Tx has been oxidized to varying degrees to produce hybrids ranging from Ti3C2Tx/TiO2 (partial MXene surface oxidation) to C/TiO2 (complete MXene oxidation).…”
Section: Design Strategies For Mxene Hybrids and Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research studies have shown that MXenes have promising potential for photocatalytic applications, due to some distinct properties: i) the high carrier mobility in MXene-based system efficiently promoting the separation and migration of photogenerated electron-hole pairs; ii) the tunable band gap of MXenes by altering their surface chemistries, for example, the terminated -F, -O, or -OH groups, or the arrangements of surface groups; iii) the abundant surface groups with more active sites on the surface of MXene. [178][179][180] It is noted that Ti 3 C 2 T x has already been employed as an efficient co-catalyst in g-C 3 N 4 , [181][182][183][184] Bi 2 WO 6 , [185] BP, [178] AgInS 2 , [65,186] SrTiO 3 , [187] hematite, [154] , anatase, [179,188,189] and so on, to further enhance their photocatalytic performance. For example, in 2018, the 2D MXene Ti 3 C 2 T x /2D g-C 3 N 4 nanosheet heterostructures were rationally designed and successfully synthesized by calcination of bulk Ti 3 C 2 and urea, where urea not only acts as the gas template to process the exfoliation of Ti 3 C 2 into Ti 3 C 2 T x nanosheets, but also as the precursor of g-C 3 N 4 to obtain 2D MXene Ti 3 C 2 T x /2D g-C 3 N 4 nanosheet heterostructures.…”
Section: Catalysismentioning
confidence: 99%
“…In the past two decades, the semiconductor photocatalysts have been greatly developed by a large number of scholars from various countries and regions. Many photocatalytic materials have been investigated, including metal oxides or sulfides, such as TiO2 [19][20][21][22][23][24][25][26][27][28], CdS [29][30][31][32][33][34][35][36][37][38] and ZnCdS [15,[39][40][41][42], and the metal-free semiconductors such as rGO [43] and g-C3N4 [5,[44][45][46][47][48][49][50][51][52][53][54]. However, the photocatalytic activities of the most promising semiconductor photocatalysts are still not quite satisfied due to the easy recombination between charge carriers.…”
Section: Introductionmentioning
confidence: 99%